High prevalence of viable Mycobacterium avium subspecies paratuberculosis in Crohn’s disease - Mendoza, Juan L (Baishideng Publishing Group Co., Limited, 2010)
AIM: To examine the detection rate of viable Mycobacterium avium subspecies paratuberculosis (MAP) in patients with inflammatory bowel disease [Crohn’s disease (CD) and ulcerative colitis (UC)]. METHODS: Thirty patients with CD (15 with at least one NOD2/CARD15 mutation), 29 with UC, and 10 with no inflammatory bowel disease (IBD). were tested for MAP by polymerase chain reaction (specific IS900 fragment) and blood culture. RESULTS: MAP DNA was detected in all original blood samples and 8-wk blood cultures (CD, UC and non-IBD). Positive MAP DNA status was confirmed by dot blot assays. All 69 cultures were negative by acid-fast Ziehl-Neelsen staining. Viable MAP, in spheroplast form, was isolated from the 18-mo blood cultures of all 30 CD patients, one UC patient, and none of the non-IBD controls. No association was found between positive MAP cultures and use of immunosuppressive drugs or CD-associated single nucleotide polymorphisms. CONCLUSION: MAP is widely present in our area and MAP DNA can be recovered from the blood of CD, UC and non-IBD patients. However, MAP spheroplasts were only found in CD patients.